2013
DOI: 10.1093/eurheartj/eht491
|View full text |Cite
|
Sign up to set email alerts
|

Device-detected atrial fibrillation and risk for stroke: an analysis of >10 000 patients from the SOS AF project (Stroke preventiOn Strategies based on Atrial Fibrillation information from implanted devices)

Abstract: ObjectiveThe aim of this study was to assess the association between maximum daily atrial fibrillation (AF) burden and risk of ischaemic stroke.BackgroundCardiac implanted electronic devices (CIEDs) enhance detection of AF, providing a comprehensive measure of AF burden.Design, setting, and patientsA pooled analysis of individual patient data from five prospective studies was performed. Patients without permanent AF, previously implanted with CIEDs, were included if they had at least 3 months of follow-up. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
281
0
13

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(300 citation statements)
references
References 22 publications
6
281
0
13
Order By: Relevance
“…Ryzyko udaru u pacjentów z AHRE wydaje się mniejsze niż u pacjentów z rozpoznaniem AF i nie wszystkie epizody AHRE oznaczają AF [142]. Udary mózgu często występują również u pacjentów, u których nie stwierdza się AHRE w ciągu 30 dni poprzedzających wystąpienie udaru [143][144][145][146][147]. W rezultacie nie jest jasne, czy AHRE wiążą się z tymi samymi wymogami terapeutycznymi, co jawne AF [148], a korzyści z OAC u pacjentów z AHRE są oceniane w trwających próbach klinicznych, np.…”
Section: Pacjenci Ze Stymulatorami I Innymi Wszczepionymi Urządzeniamiunclassified
“…Ryzyko udaru u pacjentów z AHRE wydaje się mniejsze niż u pacjentów z rozpoznaniem AF i nie wszystkie epizody AHRE oznaczają AF [142]. Udary mózgu często występują również u pacjentów, u których nie stwierdza się AHRE w ciągu 30 dni poprzedzających wystąpienie udaru [143][144][145][146][147]. W rezultacie nie jest jasne, czy AHRE wiążą się z tymi samymi wymogami terapeutycznymi, co jawne AF [148], a korzyści z OAC u pacjentów z AHRE są oceniane w trwających próbach klinicznych, np.…”
Section: Pacjenci Ze Stymulatorami I Innymi Wszczepionymi Urządzeniamiunclassified
“…Studies on community screening, 16 in patients with implanted devices, [17][18][19][20][21][22] and after ischemic stroke 14,23 have found that AF is mostly asymptomatic and would therefore remain undetected with monitoring strategies based on symptom-triggered recordings. Monitoring strategies based on algorithm-activated recordings have the potential to detect both symptomatic and asymptomatic AF.…”
Section: Device-related Factorsmentioning
confidence: 99%
“…The threshold for a significant increase of TE risk varied from 5 minutes to 24 hours. [17][18][19][44][45][46][47] It seems reasonable to speculate that the implications of AF burden may be different in patients with different baseline risks, in particular in patients with or without prior stroke. An interesting observation supporting the hypothesis of a multivariable model and the absence of a fixed threshold predictive of increased risk is suggested from a proof-of-concept study in which the risk of stroke or TE events was found to be not only a function of the time spent in AF, but also of the baseline characteristics of the patients.…”
Section: Af Burden and Risk Of Strokementioning
confidence: 99%
“…30 There is some evidence that the amount of arrhythmia in AF patients correlates with thromboembolic risk, but a large study is required to validate this finding. 34 The arrhythmic burden can be quantified with a continuous monitoring system, even though ILR data have shown a good correlation with continuous Holter monitoring. 35,36 Finally, the registration of the beginning of an AF episode with event recorders may help to establish the pathogenic mechanism of the arrhythmia.…”
Section: Holter Monitors and Loop Recorders In Patient Follow-upmentioning
confidence: 99%